Membongkar rahasia keuangan: Analisis common size pada laporan keuangan PT Sido Muncul Tbk dalam dunia industri jamu dan farmasi - Lestari, Dheri Febiyani; Herdiyanti, Herdiyanti; Agustina, Gina; Sartika, Ika (Jurnal Manajemen, 2024)
A company's financial reports describe the company's performance and finances and help stakeholders in making decisions about the company. The aim of this research is to analyze the financial reports of PT Industri Jamu dan Farmasi Sido Muncul Tbk. This research uses two main methods, namely financial ratio analysis and the common size method. The method of this research is quantitative descriptive. The financial report data used in this research are financial reports from 2020 to 2022. This data is used to determine the relative proportions of assets, liabilities and equity in the financial reports. Common size data allows analysis over time and comparison with similar companies. This research provides understanding to company stakeholders, including management, investors and decision makers, regarding the financial performance of PT Industri Jamu and Farmasi Sido Muncul Tbk and uses it as a basis for strategic decision making and financial planning for the future. Even though PT Industri Jamu dan Farmasi Sido Muncul Tbk's sales are declining, the financial position of PT Industri Jamu and Farmasi Sido Muncul Tbk which remains strong will attract special attention from stakeholders.